CHID: a unique health information and education database. - Lunin, L F (1987)
The public's growing interest in health information and the health professions' increasing need to locate health education materials can be answered in part by the new Combined Health Information Database (CHID). This unique database focuses on materials and programs in professional and patient education, general health education, and community risk reduction. Accessible through BRS, CHID suggests sources for procuring brochures, pamphlets, articles, and films on community services, programs at HMOs and hospitals, aspects of coping, and more. CHID is a joint project of six federally funded agencies in the Public Health Service. CHID provides citations with abstracts to major health journals, books, reports, pamphlets, hard-to-find information resources, and to health education programs under way in state and local health departments and other locations.